FOXP3/HAT1 Axis Controls Treg Infiltration in the Tumor Microenvironment by Inducing CCR4 Expression in Breast Cancer - Sarkar, Tania; Dhar, Subhanki; Chakraborty, Dwaipayan; Pati, Subhadip; Bose, Sayantan; Panda, Abir K.; Basak, Udit; Chakraborty, Sourio; Mukherjee, Sumon; Guin, Aharna; Jana, Kuladip; Sarkar, Diptendra K.; et al. (Frontiers in Immunology, 2022)
Infiltrating T-regulatory cells in the tumor microenvironment is a key impediment to immunotherapy and is linked to a poor prognosis. We found that tumor-infiltrating Tregs express a higher expression of the chemokine receptor CCR4 than peripheral Tregs in breast cancer patients. CCL22 and CCL17 are released by tumor cells and tumor-associated macrophages, attracting CCR4+ Tregs to the tumor site. The Treg lineage-specific transcription factor FOXP3 changes the CCR4 promoter epigenetically in conjunction with HAT1 to provide a space for FOXP3 binding and activation of the CCR4 gene. To increase CCR4 expression in Tregs, the FOXP3/HAT1 axis is required for permissive (K23 and K27) or repressive (K14 and K18) acetylation of histone-3. In murine breast and melanoma tumor models, genetic ablation of FOXP3 reduced CCR4+ Treg infiltration and tumor size while also restoring anti-tumor immunity. Overexpression of FOXP3, on the other hand, increased CCR4+ Treg infiltration, resulting in a decreased anti-tumor immune response and tumor progression. These findings point to FOXP3 playing a new role in the tumor microenvironment as a transcriptional activator of CCR4 and a regulator of Treg infiltration.